Predictors Of Flourishing Among Elderly In Penang, Malaysia: The Role Of Demographic Variables And Perma Elements - Liew, Wei Peng (2022)
Flourishing is a state of optimal mental well-being. It is the experience of doing and living well in all aspects of one's life, including psychological and social well-being. Flourishing plays a significant role in all life span, and every person has the potential to flourish. Elderly as the growing age group in Malaysia can benefit from being flourished. Nevertheless, current approach to studying flourishing is too general and limited studies have focused on flourishing, particularly among Malaysian elderly from a heterogeneous society with diverse cultural backgrounds. Each ethnicity has its own definition of what it means to flourish. By understanding the definitions of each ethnicity, interventions, programs, or measurements of those who flourish and those who do not can be taken appropriately. As a result, this study focuses on the role of demographic variables (e.g., age, gender, ethnicity, religion, marital status, source of income and education attainment) and elements in PERMA (e.g., engagement, positive relations with others, meaning in life and accomplishment) in contributing to flourishing among Malaysian elderly from various races.